Conselhos municipais na administração do Movimento Democrático Brasileiro (MDB): análise de Guaíba/RS (2001-2008) - Santos, Mauricéia Alves dos (Universidade do Vale do Rio dos Sinos, 2023)
This study seeks to understand the place occupied by the municipal councils implemented during the administration of the Brazilian Democratic Movement (MDB) party, during the period from 2001 to 2008. Therefore, the empirical investigation was based on a qualitative case study conducted in the municipality of Guaíba/RS, focusing the analysis on the councils of weak or no induction of federal resources to be implemented. Data collection used materials collected from documentary research, bibliographic research and semi-structured interviews. The theoretical framework starts from the Theories of Non-hegemonic Democracies based on the "Deliberative" and "Participatory" perspectives, in addition to bringing the review of the literature on Participatory Institutions, which focused on the councils implemented after the promulgation of the 1988 Constitution, as well as the studies related to social participation and the MDB party. In the course of this debate, the data evidenced the understanding that the municipal councils are beyond their institutional functions, serving as a channel of articulation between the party and the community leaders along the lines of those councils implemented during the 1980s. Although there has been an expansion of participation through the councils, other mechanisms of institutionalized participation were not part of the party's government project, in addition to the lack of an emancipatory and educational participation that enables the population to participate effectively in the implementation and execution of public policies. This leads us to question what is in fact the place occupied by social participation in MDB party administrations.
Keywords: Instituições participativas; Participação social; Conselhos municipais; Movimento Democrático Brasileiro, MDB; Participatory institutions; Social participation; Municipal councils; Brazilian Democratic Movement, MDB; ACCNPQ::Ciências Humanas::Sociologia